Relationship between spiritual health and clinical competency of nurses working in intensive care units - Amir Jalali; Mahmoud Rahmati; Bita Dastmozd; Nader Salari; Mohammad-Rafi Bazrafshan (Shiraz University of Medical Sciences, 2019)
Introduction: Spiritual health is the newest dimension of health that lies alongside other aspects of health. Since few studies have been conducted on the various effects of spirituality on nurses' clinical competence, this study aimed to determine the relationship between spiritual health and clinical competency of nurses. Methods: This study is a cross-sectional study. The samples consisted of 135 nurses working in intensive care units affiliated to Iran University of Medical Sciences. According to the number of nursing staff in each ward, the share of each ward was determined, and then nurses selected by random sampling.  Data were collected using the Spiritual Well-Being questionnaire and the Critical Care Nursing Competence Scale. After referring to the wards, the questionnaires were compiled by the researchers, and finally, it was analyzed using the Pearson correlation coefficient test. The significance level was considered to be 5%. Results: The mean age of nurses was 35±6.6 years, their mean clinical experience was 11±7 years and the mean of nurses' work experience was 6.95±5 years. The mean score of spiritual well-being was 79.29±4.33 (medium level), the mean score of clinical competence was 378.53±4.90 (excellent condition) and the mean score of professional competence was 310.95±3.14 (excellent condition). Correlation test results showed no significant statistical relationship between spiritual health and clinical competency dimensions (P value>0.05).There was also no significant relationship between dimensions of spiritual health (existential health and religious health) and nurses' clinical competency (P-value>0.05). Conclusion: Nurses in ICUs have a relatively high and acceptable level of spiritual health and clinical competence, but nurses' clinical competence is not directly related to their spiritual health.